BAHASA LOKAL SULAWESI TENGGARA DALAM DUNIA PENYIARAN - Najib Husain; M. Ishak Syahadat; Dewi Anggraini (Journal Publicuho, 2023)
This article explores the use of local languages in the broadcasting world on community radio in Southeast Sulawesi in conveying messages to listeners so that they are more easily accepted. This paper takes the case of community radio in Konawe, Buton and Wakatobi districts. This research uses a descriptive qualitative method (Moeloeng, 2005). Data collection techniques are used by collecting secondary data and primary data. Secondary data was obtained through document collection from community radios in Southeast Sulawesi. Furthermore, primary data was obtained through the researcher's field notes and the results of interviews with informants. Again, the collected data is sorted and then selected using triangulation techniques. The use of local languages in the broadcasting world, from the results of research that has been carried out by community radios in Southeast Sulawesi, namely Suara Marannu Radio on Saponda Island, Pasihuang FM Radio in Mekar Village, Soropia District which uses the Bajo language, Talombo FM Radio on Tomia Wakatobi Island which uses the Indonesian language Tomia, and Sinar Lapandewa Radio in Buton which uses Cia-Cia language. Use of Local Languages in broadcasting activities. Efforts made by community radio managers to oblige broadcasters to use regional languages are nothing but a filter against the presence of slang, Alay and Jakarta accents which are widely used by broadcasters in greeting young people in Indonesia which will certainly cause the next generation to be foreign. in his own language.